Australian perspectives on spiritual care training in healthcare: A Delphi study. Issue 6 (December 2021) - Jones, Kate F.; Washington, Jennifer; Kearney, Matthew; Kissane, David; Best, Megan C.
Abstract: Objective: The aim was to to establish core components of spiritual care training for healthcare professionals in Australia. Methods: This study used the Delphi technique to undertake a consensus exercise with spiritual care experts in the field of healthcare. Participant opinion was sought on (i) the most important components of spiritual care training; (ii) preferred teaching methods; (iii) clinical scenarios to address in spiritual care training; and (iv) current spiritual assessment and referral procedures. Results: Of the 107 participants who responded in the first round, 67 (62.6%) were female, 55 (51.4%) worked in pastoral care, and 84 (78.5%) selected Christian as their religious affiliation. The most highly ranked components of spiritual care training were "relationship between health and spirituality, " followed by "definitions of spirituality and spiritual care." Consensus was not achieved on the item "comparative religions study/alternative spiritual beliefs." Preferred teaching methods include case studies, group discussion, role-plays and/or simulated learning, videos of personal stories, and self-directed learning. The most highly ranked clinical scenario to be addressed in spiritual care training was "screening for spiritual concerns for any patient or resident." When asked who should conduct an initial spiritual review with patients, consensus was achieved regarding all members of the healthcare team, with most nominating a chaplain or "whoever the patient feels comfortable with." It was considered important for spiritual care training to address one's own spirituality and self-care. Consensus was not achieved on which spiritual care assessment tools to incorporate in training. Significance of results: This Delphi study revealed that spiritual care training for Australian healthcare professionals should emphasize the understanding of the role of spirituality and spiritual care in healthcare, include a range of delivery methods, and focus upon the incorporation of spiritual screening. Further work is required to identify how spiritual care screening should be conducted within an Australian healthcare setting.